Trocar-site hernia after gynecological laparoscopic surgery: a 20-year, single-center experience - Zhu, Ya-Pei (Chin Med J (Engl), 2019)
BACKGROUND: Trocar-site hernia (TSH) is a serious complication after laparoscopic procedures. Although it is a rare entity, it can have life-threatening consequences. This study aimed to retrospectively analyze the potential associated factors for TSH following gynecologic laparoscopy and summarize prevention strategies based on our experience. METHODS: We searched for gynecological laparoscopic surgeries in the medical records system of Peking Union Medical College Hospital (PUMCH) from August 1998 to July 2018 and further sifted through the results for cases involving TSH. All included patients were divided into different groups according to patient characteristics, and the rate of TSH was compared among groups. Moreover, the detailed information of all patients with TSH was recorded and analyzed. Statistical analyses were performed with GraphPad Prism 6. RESULTS: The approximate total rate of post-operative TSH among gynecologic laparoscopy procedures performed at PUMCH in the last 20 years was 0.016% (9/55,244). The rate of TSH was significant higher in elder patients (≥60 years old; 3/2686, 0.112%) than in younger patients (<60 years old, 6/52,558; 0.011%, P = 0.008). Moreover, the approximate rate of TSH was significantly higher after single-incision laparoscopic surgery (SILS, 2/534, 0.357%) than conventional laparoscopic surgery (7/54,710, 0.013%, P = 0.003). The average age of patients with TSH was 53.4 years (range, 35.0–79.0 years). Two of the nine patients had late-onset TSH following SILS; the other seven had early-onset TSH following conventional laparoscopy. Five TSH cases occurred at right lateral port sites, and the remaining three occurred at the umbilical port site. All patients underwent repair surgery, and one required small bowel resection. CONCLUSION: Older age and SILS are potential associated factors for TSH development, while reducing excessive manipulation and improving suturing skills, especially at the umbilical trocar site following SILS and the right lateral trocar site, can avoid herniation.